2015
DOI: 10.1177/1087057114554170
|View full text |Cite
|
Sign up to set email alerts
|

Assays, Surrogates, and Alternative Technologies for a TB Lead Identification Program Targeting DNA Gyrase ATPase

Abstract: Mycobacterium tuberculosis (Mtb) DNA gyrase ATPase was the target of a tuberculosis drug discovery program. The low specific activity of the Mtb ATPase prompted the use of Mycobacterium smegmatis (Msm) enzyme as a surrogate for lead generation, since it had 20-fold higher activity. Addition of GyrA or DNA did not significantly increase the activity of the Msm GyrB ATPase, and an assay was developed using GyrB alone. Inhibition of the Msm ATPase correlated well with inhibition of Mtb DNA gyrase supercoiling acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To prove our hypothesis, we chose Mycolicibacterium smegmatis as a tuberculosis model. 11 Different concentrations of the hit peptides were incubated with the culture media, from 12.5 μM to 100 μM, for 3 days, and growth inhibition was measured via bacterial counting. Interestingly, both SMMMC and SCGMM exhibited a dose-dependent growth inhibition trend, and SMMMC and SCGMM inhibited the growth of M. smegmatis by up to 40% and 25%, respectively, at 100 μM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To prove our hypothesis, we chose Mycolicibacterium smegmatis as a tuberculosis model. 11 Different concentrations of the hit peptides were incubated with the culture media, from 12.5 μM to 100 μM, for 3 days, and growth inhibition was measured via bacterial counting. Interestingly, both SMMMC and SCGMM exhibited a dose-dependent growth inhibition trend, and SMMMC and SCGMM inhibited the growth of M. smegmatis by up to 40% and 25%, respectively, at 100 μM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B6C codes for the structure of M. smegmatis GyrB ATPase domain in complex with an aminopyrazinamide, a known inhibitor of the GyrB [71]. The use of M. smegmatis as a surrogate for M. tuberculosis has been previously demonstrated in the literature, as a result of Mtb’s low specific activity [72] and slow growth [71]. Also, Saxena et al [45] did a sequence alignment of the M. smegmatis and M. tuberculosis DNA GyrB and found that they share 87.4% similarity.…”
Section: Resultsmentioning
confidence: 99%